2011
DOI: 10.1074/jbc.m111.260133
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Endoglin Specifically Binds Bone Morphogenetic Proteins 9 and 10 via Its Orphan Domain, Inhibits Blood Vessel Formation, and Suppresses Tumor Growth

Abstract: Endoglin (CD105), a transmembrane protein of the transforming growth factor ␤ superfamily, plays a crucial role in angiogenesis. Mutations in endoglin result in the vascular defect known as hereditary hemorrhagic telangiectasia (HHT1). The soluble form of endoglin was suggested to contribute to the pathogenesis of preeclampsia. To obtain further insight into its function, we cloned, expressed, purified, and characterized the extracellular domain (ECD) of mouse and human endoglin fused to an immunoglobulin Fc d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
229
4
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(255 citation statements)
references
References 38 publications
12
229
4
3
Order By: Relevance
“…Also, in clinical development as an antitumor agent is a chimeric antibody (TRACON) capable of neutralizing endoglin (CD105; ref. 31), a proangiogenic protein in the TGFb superfamily that binds BMP9/BMP10 (22,45,46), with loss-of-function mutations resulting in another type of vascular dysplasia, HHT-1 (15,47). In patients with advanced, refractory tumors (31), anti-endoglin antibody was associated with infusion reactions and immunogenicity distinct from effects described for dalantercept in the present study, whereas other adverse effects such as anemia and telangiectasias were observed in both studies.…”
Section: Discussioncontrasting
confidence: 44%
“…Also, in clinical development as an antitumor agent is a chimeric antibody (TRACON) capable of neutralizing endoglin (CD105; ref. 31), a proangiogenic protein in the TGFb superfamily that binds BMP9/BMP10 (22,45,46), with loss-of-function mutations resulting in another type of vascular dysplasia, HHT-1 (15,47). In patients with advanced, refractory tumors (31), anti-endoglin antibody was associated with infusion reactions and immunogenicity distinct from effects described for dalantercept in the present study, whereas other adverse effects such as anemia and telangiectasias were observed in both studies.…”
Section: Discussioncontrasting
confidence: 44%
“…Because ALK1 is known to bind the co-receptor endoglin upon ligand binding (15,16), we subsequently examined the effect of anti-hALK1 antibody on ALK1-endoglin complex formation. In HEK293T cells, human ALK1-HA and human endoglin-FLAG were co-transfected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ALK1 and endoglin have been shown to engage in a complex, although whether this is ligand-dependent or -independent is debated (15,16).…”
mentioning
confidence: 99%
“…Although a member of the BMP subfamily and possessing chondrogenic and osteogenic activity, BMP9 is expressed in liver and is required for properly organized blood and lymphatic vascular development (11,12). Mutations in the prodomain of BMP9, in its receptor Alk1, and in its coreceptor endoglin cause phenotypically overlapping hereditary hemorrhagic telangiectasias (13)(14)(15).…”
mentioning
confidence: 99%